Nitration Transforms a Sensitive Peroxiredoxin 2 into a More Active and Robust Peroxidase - Randall, Lía M. (American Society for Biochemistry and Molecular Biology, 2014)
Peroxiredoxins (Prx) are efficient thiol-dependent peroxidases and key players in the mechanism of H(2)O(2)-induced redox signaling. Any structural change that could affect their redox state, oligomeric structure, and/or interaction with other proteins could have a significant impact on the cascade of signaling events. Several post-translational modifications have been reported to modulate Prx activity. One of these, overoxidation of the peroxidatic cysteine to the sulfinic derivative, inactivates the enzyme and has been proposed as a mechanism of H(2)O(2) accumulation in redox signaling (the floodgate hypothesis). Nitration of Prx has been reported in vitro as well as in vivo; in particular, nitrated Prx2 was identified in brains of Alzheimer disease patients. In this work we characterize Prx2 tyrosine nitration, a post-translational modification on a noncatalytic residue that increases its peroxidase activity and its resistance to overoxidation. Mass spectrometry analysis revealed that treatment of disulfide-oxidized Prx2 with excess peroxynitrite renders mainly mononitrated and dinitrated species. Tyrosine 193 of the YF motif at the C terminus, associated with the susceptibility toward overoxidation of eukaryotic Prx, was identified as nitrated and is most likely responsible for the protection of the peroxidatic cysteine against oxidative inactivation. Kinetic analyses suggest that tyrosine nitration facilitates the intermolecular disulfide formation, transforming a sensitive Prx into a robust one. Thus, tyrosine nitration appears as another mechanism to modulate these enzymes in the complex network of redox signaling.